Rhupus Syndrom in a Young Male Patient: A Rare Case - Gede Indra Dananjaya, Putu; Made Putri Purnama Dewi, Ni (International Journal of Psychology and Health Science, 2024)
Rhupus syndrome refers to the simultaneous presence of systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA). Rhupus syndrome exhibits a higher prevalence in female and rarely in male, similar to systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA). Upon examining the literature, it is evident that the majority of case reports consist of female patients. This case report describes a male patient who diagnosed with rhupus syndrome. Case Report: We report the case of a 27-year-old male patient who based on the SLE-SLICC 2012 criteria, the patient met the diagnosis criteria of SLE. Based on the 2010 ACR/EULAR criteria, the patient was diagnosed with rheumatoid arthritis with a total score of 9. The joint criteria showed involvement of more than 10 joints with at least 1 large joint, positive rheumatoid factor results, high CRP and ESR levels, and symptom duration of more than 6 weeks. Discussion: Rhupus syndrome is a condition characterized by a symmetric polyarthritis which leads to deformation and erosion. It is preceded by symptoms and signs of SLE and the presence of antibodies that are very specific for diagnosis, such as anti-double stranded DNA, anti-Smith, and anti-cyclic citrullinated peptide. Conclusion: In this case, the timely detection of rhupus syndrome is crucial in order to select appropriate treatments, minimize potential complications, and enhance the patient's prognosis, despite its rarity.